The History of the Romanian System of Public Administration. The Public Administration of the Royal Dictatorship and the Nationality Question - Zsolt SZÉKELY (Transylvanian Review of Administrative Sciences, 2009)
The goal of the present study is to explore aunique system of public administration that wascarried out during the dictatorship of Charles IIin Romania between the two World Wars. In aparadoxical manner, the only effort to solve thenationality question through legislation tookplace under his royal dictatorship. In 1938, thegovernment published its three-part collection oflaws, known as the Minority Statute, which definedthe rights of minorities. The Minority Statute wasintended primarily for foreign publication, and itwas addressed more toward a foreign audience,which is also illustrated by the fact that it was onlypublished in the official newspaper, and censorshad prohibited it from being published in eitherthe majority or the minority press. Among thecircumstances surrounding the creation of theMinority Statute, it is interesting to note that theMinistry of Foreign Affairs played the largest rolein its drafting process.